The World of science. - Taylor, F. Sherwood (London William Heinemann, 1936)
Each volume contains topically arranged science articles and a dictionary of scientific terms. Alphabetically arranged biographies of about 500 scientists are included in volumes nineteen and twenty.
Cover title: Illustrated world of science encyclopedia.
Translated and adapted from Scienza: enciclopedia tecnica e scientifica.
Keywords: Science -- Encyclopedias, Juvenile; Science -- Encyclopedias